Livestock production in central Mali: Environmental and pathological factors affecting morbidity and mortality of ruminants in the agropastoral system - Traoré, A.; Wilson, R.T. (Elsevier, 1988)
Looks at morbidity and mortality levels of domestic ruminants as influenced by environmental and pathological factors in a traditional agropastoral production system in the Niono area in central Mali. Examines causes and rates of morbidity and mortality and percentage and levels of gastro-intestinal infestation of central Mali ruminants.